Carbon flow web model for the inner and outer Beagle Channel (Sub-Antarctica) during springtime - Marina, Tomas Ignacio (2024)
The Beagle Channel (BC) constitutes a unique sub-Antarctic coastal ecosystem connecting the Pacific and Atlantic oceans at the southern tip of South America. It is also considered a spatially variable atmospheric CO2 sink. The presence of sills in the BC originates micro-basins which favour the formation of particular biological niches in terms of nutrients, primary production and planktonic communities. Here we developed a mass-balanced carbon flow model for the pelagic ecosystem of BC for the spring season, focusing on two contrasting sites: the inner and outer channel to the west and east of the Mackinlay Strait, respectively. For this, we used a single model for both study sites since the structure of the pelagic community is similar in both sectors of the BC. In order to reflect the differences among sites, we parameterized the model according to each case, inner and outer, mostly considering empirical data gathered during the binational Argentine-Chilean campaign carried out in 2019. The model comprises ten compartments representing the key components of the pelagic community of the BC (e.g., phytoplankton, microzooplankton (67-200 μm), mesozooplankton (200-20000 μm), ichthyoplankton). Our results show important quantitative differences in the carbon sources produced within the pelagic ecosystem (autochthonous), such as phytoplankton, and that imported (allochthonous), such as terrestrial input, between the inner and outer BC. Noteworthy, benthic resuspension provides as much carbon as the allochthonous source to the pelagic ecosystem in both sites.Overall, these preliminary results suggest a differential energy flow pattern during spring in the inner and outer BC pelagic ecosystems.